(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nurlela, Nurfalah R, Ananda F, Ridwan T, Ilmiawati A, Nurcholis W, Takemori H, Batubara I. 2022. Variation of morphological characteristics, total phenolic, and total flavonoid in Adenostemma lavenia, A. madurense, and A. platyphyllum. Biodiversitas 23: 3999-4005. Adenostemma has long been used as a herbal medication. Despite some studies regarding the morphology and potency of Adenostemma carried out, the variation of morphological traits, total phenolic content (TPC), and total flavonoid content (TFC) on different species of Adenostemma has been poorly investigated. This study was designed to observe the morphological characteristics, TPC, and TFC of Adenostemma lavenia, A. madurense, and A. platyphyllum. Morphological characteristics were observed using qualitative and quantitative parameters. The colorimetric method determined TPC and TFC in plant leaf ethanol extracts. The plants were morphologically diverse, which significant variation among the three species in plant height, length and width of leaf, and internodes distance. Morphological traits such as leaf length and width, plant height, and internodes distance significantly correlate with phenolic and flavonoid content in Adenostemma. These may be used as important selection criteria in Adenostemma for obtaining high phenolic and flavonoid content. The study revealed that different species of these plants with varying morphological traits substantially impact the content of their chemical compounds. The highest TPC and TFC were found in A. lavenia, suggesting that it is potentially an alternative source of bioactive compounds as herbal medicine.